Physicians’ Concerns About Synopses of Clinical Research - Pluye, Pierre; Grad, Roland; Johnson-Lafleur, Janique; Shulha, Michael (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Health professionals may follow original research via synopses received on e-mail. Synopses are written from original studies selected for validity and relevance. We explored professionals’ concerns about synopses (qualitative multiple case study). Of 28 participants, 17 (60.7%) reported concerns: 15 with the content of synopses and four with the format. Les professionnels de la santé reçoivent des synopsis de recherche originale par courriel (synopsis d’articles sélectionnés pour leur pertinence et leur validité). Nous avons exploré les préoccupations des professionnels concernant les synopsis (étude de cas multiple – recherche qualitative). Parmi 28 participants, 17 (60,7 %) avaient des préoccupations : 15 avec le contenu des synopsis et quatre avec le format.